Analysis of the Community Satisfaction Index at Satpol Pp and Damkar of South Bengkulu Regency - Sindi Triani; Neri Susanti (Penerbit Jurnal Indonesia, 2023)
Good public service refers to a person's level of satisfaction with what is received, either an individual's relationship with an individual or an individual's relationship with a government agency. Government agencies as public service providers have efforts to improve the quality of public services, one of which is the Civil Service Police Unit and Fire Department of South Bengkulu Regency. To obtain and analyze data on the level of public satisfaction with the implementation of public services that have been provided by the Civil Service Police Unit and the Fire Department of South Bengkulu Regency. Research methods can be interpreted as tools to answer certain questions and to solve scientific or practical problems. In this study the authors used descriptive quantitative research methods. Based on the results of research and discussion, it can be concluded as follows: Based on the calculation of the Community Satisfaction Index which refers to Kepmenpan RB No. 25 of 2018, the Satpol PP and Fire Fighters Office of South Bengkulu Regency obtained an IKM Conversion result of 50.5. The performance of the Mungkid District Office service unit is in the